'Hello, MaxFax on-call?' – maxillofacial 'bleep sheet' proforma for on-call referrals. Issue 7 (September 2021) - Donnell, C.C.; Mamidela, R.; Swinson, B.D.
Abstract: The on-call component of a dental core training (DCT) post in oral and maxillofacial surgery (OMFS) is considered to be the most daunting and challenging aspect of the job. The average trainee is a singly-qualified dentist with limited knowledge and experience of managing OMFS presentations. Given the short duration of DCT posts, there is a continual rotation of junior staff through OMFS departments with a varying skillset and knowledge mix. As such, the consistent recording of appropriate information remains a constant challenge. The coronavirus pandemic has presented a unique situation in which the majority of dental foundation trainees (DFTs) entering OMFS DCT posts will only have around six months experience of independent practice. This lack of experience and onerous on-call workload could be a potentially dangerous combination, especially during nightshift patterns of on-call. We demonstrate that implementation of an on-call bleep-sheet proforma provides a validated, standardised, systematic, and chronological method of record keeping that exceeds the minimum required standard of clinical governance, in an era where junior trainees entering OMFS will have had even more limited experience than normal.